show this by your explanation
1+cos^2 a /sin^2 a = 2cosec a -1
Answers
Answered by
3
Hey friend,
The question should be -
1 + cos^2A / sin^2A = 2 cosec^2A - 1
LHS
= 1/sin^2A + cos^2A/sin^2A (splitting the numerator)
= cosec^2A + cot^2A (cotA = cosA/sinA)
= cosec^2A + cosec^2A - 1 (cot^2A = cosec^2A - 1)
= 2 cosec^2A - 1
=RHS
LHS = RHS
Hence Proved!
Hope it helps!
The question should be -
1 + cos^2A / sin^2A = 2 cosec^2A - 1
LHS
= 1/sin^2A + cos^2A/sin^2A (splitting the numerator)
= cosec^2A + cot^2A (cotA = cosA/sinA)
= cosec^2A + cosec^2A - 1 (cot^2A = cosec^2A - 1)
= 2 cosec^2A - 1
=RHS
LHS = RHS
Hence Proved!
Hope it helps!
rohitkumargupta:
Well
Answered by
4
Hello friend
___________________________
Here is your answer!!!
Take L.H.S
![\frac{1 + cos {}^{2} a}{sin {}^{2}a } \\ \\ => \frac{1}{sin {}^{2}a \: } + \frac{cos {}^{2} a}{sin {}^{2} a} \frac{1 + cos {}^{2} a}{sin {}^{2}a } \\ \\ => \frac{1}{sin {}^{2}a \: } + \frac{cos {}^{2} a}{sin {}^{2} a}](https://tex.z-dn.net/?f=+%5Cfrac%7B1+%2B+cos+%7B%7D%5E%7B2%7D+a%7D%7Bsin+%7B%7D%5E%7B2%7Da+%7D+%5C%5C+%5C%5C+%3D%26gt%3B+%5Cfrac%7B1%7D%7Bsin+%7B%7D%5E%7B2%7Da+%5C%3A+%7D+%2B+%5Cfrac%7Bcos+%7B%7D%5E%7B2%7D+a%7D%7Bsin+%7B%7D%5E%7B2%7D+a%7D+)
![=>cosec {}^{2} a + cot {}^{2} a \\ \\ =>cosec {}^{2} a \: + \: cosec {}^{2}a - 1 \\ \\=> 2cosec {}^{2} a \: - 1 \\ \\ =>cosec {}^{2} a + cot {}^{2} a \\ \\ =>cosec {}^{2} a \: + \: cosec {}^{2}a - 1 \\ \\=> 2cosec {}^{2} a \: - 1 \\ \\](https://tex.z-dn.net/?f=%3D%26gt%3Bcosec+%7B%7D%5E%7B2%7D+a+%2B+cot+%7B%7D%5E%7B2%7D+a+%5C%5C+%5C%5C+%3D%26gt%3Bcosec+%7B%7D%5E%7B2%7D+a+%5C%3A+%2B+%5C%3A+cosec+%7B%7D%5E%7B2%7Da+-+1+%5C%5C+%5C%5C%3D%26gt%3B+2cosec+%7B%7D%5E%7B2%7D+a+%5C%3A+-+1+%5C%5C+%5C%5C+)
: L.H.S = R.H.S
We have proved...
Thanks..
:)
___________________________
Here is your answer!!!
Take L.H.S
: L.H.S = R.H.S
We have proved...
Thanks..
:)
Similar questions